Formulation and evaluation of an Aloe vera -Licorice combination topical gel: a potential choice for wound healing - Fatemeh Ahmadi (Trends in Pharmaceutical Sciences, 2017)
Wound healing is a natural body response to injury and consists of three steps; Inflammation, proliferation and remodeling. Natural products have always been attractive in pharmacy and drug delivery and have shown higher patient compliance in some treatments. Aloe vera and licorice extract have each been used to improve and accelerate wound healing. It seems that combination of these two natural products may show better and effective results. Aloe vera gel and licorice extract powder were standardized with their major and important components, Glycyrrhizin and Glucomannan, respectively. Three different polymers in three different concentrations were used to prepare topical gels containing Aloe vera gel and licorice extract powder. Gels were examined for different properties such as appearance, pH, viscosity, spreadability, drug content and in vitro release. Optimized formulations contained carbopol 2% (F3) and CMC 3% (F5) with pH (5.92 and 5.69), spreadability (51 and 55 mm), a shear thinning manner and in vitro release within 8 hours proper for topical use. Preclinical studies should be processed to determine the suitability of these gels for wound healing.